Status Hukum Jasa Penyebrangan Ditinjau Dari Peraturan Lalu Lintas Dan Angkutan Jalan - Mukti, Tarzet Prasetyo; Ruslie, Ahmad Sholikhin (Journal Evidence Of Law, 2024)
Road crossing services, also known as "Pak Ogah or Cepek Police" are people who regulate traffic unofficially in return for modest money who do not have a permanent job and consider it an opportunity that can be exploited and make money in exchange for traffic control services. Some people consider the actions of road users to cross the road, some feel very helpful. This study aims to analyze crossing services in the perspective of traffic law no. 22 of 2009 concerning road traffic and transportation. The type of research used is normative by using the statutory approach, the conceptual approach. The results of this study obtained that the existence of crossing services is not regulated in Law no. 22 of 2009 concerning Road Traffic and Transportation. Basically, any person or group of people who do not have the authority are prohibited from controlling traffic at crossroads, bends or roundabouts with the intention of getting compensation for services. This traffic control activity is carried out by individuals or an organized group of people with the intention of obtaining monetary rewards. Positive law in Indonesia itself has regulated what victims are entitled to when a Traffic Accident occurs in general as stated in Article 240 of Law Number 22 of 2009 concerning Road Traffic and Transportation.